The Risk of Hearing Impairment From Ambient Air Pollution and the Moderating Effect of a Healthy Diet: Findings From the United Kingdom Biobank - Yuan, Lanlai; Li, Dankang; Tian, Yaohua; Sun, Yu (Frontiers in Cellular Neuroscience, 2022)
The link between hearing impairment and air pollution has not been established, and the moderating effect of a healthy diet has never been investigated before. The purpose of this study was to investigate the association between air pollution and hearing impairment in British adults aged 37 to 73 years, and whether the association was modified by a healthy diet. We performed a cross-sectional population-based study with 158,811 participants who provided data from UK Biobank. A multivariate logistic regression model was used to investigate the link between air pollution and hearing impairment. Subgroup and effect modification analyses were carried out according to healthy diet scores, gender and age. In the fully adjusted model, we found that exposure to PM10, NOX and NO2 was associated with hearing impairment (PM10: odds ratio [OR] = 1.15, 95% confidence interval [95% CI] 1.02 - 1.30, P = 0.023; NOX: OR = 1.02, 95% CI 1.00 - 1.03, P = 0.040; NO2: OR = 1.03, 95% CI 1.01 - 1.06, P = 0.044), while PM2.5 and PM2.5 absorbance did not show similar associations. We discovered an interactive effect of age and air pollution on hearing impairment, but a healthy diet did not. The findings suggested that exposure to PM10, NOX and NO2 was linked to hearing impairment in British adults, whereas PM2.5 and PM2.5 absorbance did not show similar associations. These may help researchers focus more on the impact of air pollution on hearing impairment and provide a basis for developing effective prevention strategies.